2017
DOI: 10.1002/bdm.2060
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Decision Makers' Eye Movements with (Un)Predictable Object Locations

Abstract: We propose a new approach for guiding eye movements by controlling the predictability of object locations. We hypothesize that when a high (low) relevance object has a predictable location, observers are more (less) likely to fixate it compared with objects in unpredictable locations. We tested this hypothesis in three decision‐making studies, manipulating the location of a product label in an unpredictable, a predictable, and a mixed visual environment. In Study 1 and Study 2, we find that participants are le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Even though visual attention data revealed that participants paid greater attention to the plant images and container types, the results imply that greater attention to the plant image and container types did not factor into consumers’ bidding process. These results were in line with recent evidence [18,52,67].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Even though visual attention data revealed that participants paid greater attention to the plant images and container types, the results imply that greater attention to the plant image and container types did not factor into consumers’ bidding process. These results were in line with recent evidence [18,52,67].…”
Section: Resultssupporting
confidence: 93%
“…Even though different knowledge and pollinator conservation involvement based respondent groups showed distinct visual attention patterns, these differences in visual attention may or may not necessarily impact participants’ bidding decisions. Consistent with Orquin et al (2018) [67], the regression results showed mixed messages about gaze cascade effects across the groups that differed in their knowledge and conservation practice involvement. For the self-perceived neonicotinoid knowledgeable group, there was no evidence that first/last fixation to the neonicotinoid labels or plant images led to changes in their bid values relative to their not knowledgeable counterparts.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…They show that repeated choices reinforce the ease of finding relevant information and that through the sequence of choice tasks, respondents become more selective and faster at acquiring that information. Orquin, Chrobot, and Grunert (2018) further demonstrate that predictability of the location of the information, which is the case in the CBC, increases (decreases) the likelihood of looking at information of high (low) relevance. That is, while eye movements are generally a result of both bottom-up (e. g., size of the stimuli), and top-down (e. g., consumer goals) factors, due to the learning that occurs in repeated choices, the latter seems to prevail (Orquin, Bagger, and Loose 2013).…”
Section: Eye Tracking Decision-making and Choicementioning
confidence: 73%
“…Decision makers often wish to ignore health, safety, or medical information when this information leads to unpleasant emotions or urges them to take undesirable actions (Sweeny et al 2010). Recent work by Orquin, Chrobot, and Grunert (2017) has shown that the predictability of object locations plays a role in our ability to fixate on interesting objects and ignore Applied Economic Perspectives and Policy irrelevant ones. The authors have shown that an unpredictable location increases attention to otherwise ignored nutrition labels.…”
Section: Unpredictable Locationsmentioning
confidence: 99%